Development of Adaptation Tools for Pupils on the Autism Spectrum in Microsystems - Alvyra Galkiene; Giedre Puskoriene (Research in Social Sciences and Technology- OpenED Network, 2020)
This research investigates the possibilities for the development of adaptation tools for pupils on the autism spectrum (AS), studying in the first and second forms, within their microsystems. Five mothers and five teachers of children on the AS participated in the research, and their insights help reveal the process of moving from one microsystem to another for a child on the AS. Children studying in the first and second forms were chosen because children experience a particularly significant social turning-point during this period. The following question is raised: How do synergy-driven processes taking place in the microsystems of pupils on the AS contribute to the development of the adaptation processes in these children? The research data was collected via semi-structured interviews and underwent qualitative content analysis. The research results reveal that the development of adaptation tools in children on the AS is determined by a mesosystem that covers various combinations of microsystems, and the synergy between the factors of the microsystems creates conditions for a child’s gradual transfer from one microsystem to another, perceiving the mechanisms of its functioning, and adapting within them. A mesosystem, which evolves on the school campus, within a family, and with specialists, not only encourages the development of adaptation tools in a child on the AS but also helps mothers to restore their inner harmony and actively engage in their children’s education process. In the microsystem of their peers, children on the AS acquire fundamental instruments for participation in community activities.